The Effect of Selenium Nanoparticles on the Expression of MexB Gene of Pseudomonas aeruginosa Isolated from Wound and Burn Infections - Maryam Salman; Nada Al-Mudallal; Mais Ahmed (The Iraqi Journal of Medical Sciences)
Background: The World Health Organization lists the Pseudomonas aeruginosa (P. aeruginosa) bacteria as a major antibiotic-resistant priority pathogen, which function as an opportunistic pathogen and causes nosocomial infections. Objective: To biosynthesize selenium nanoparticles (SeNP) using bacteriocin from Acinetobacter bumannii (A. bumannii) and to evaluate the effect on the expression of MexB gene that is responsible for the multidrug resistance (MDR) in P. aeruginosa. Methods: Using an agar well diffusion assay, the first screening process evaluated the effect of bacteriocin-like inhibitory substance (BLIS) derived from A. baumannii on MDR P. aeruginosa. SeNP were synthesized biologically then analyzed and characterized using several techniques. The biosynthesized nanoparticles were identified, and the chemical and physical characteristics of the final product were determined, using atomic force microscope (AFM), scanning electron microscope (FESEM), energy dispersive X-ray (EDX), X-ray diffraction (XRD), and UV visible spectrometry. Results: The findings revealed a 24 mm substantial inhibitory zone of peptone water was shown to be the most appropriate supply of nitrogen, and glucose to be the best carbon source under the ideal circumstances for the synthesis of bacteriocin-like BLIS. The hexagonal structure was confirmed by XRD, and the dispersion and roughness of the nanoparticles were shown by AFM investigation revealed the 81.23 nm size range. MexB gene were found in each of the nine strains. The effect of the SeNP on the expression of the MexB gene demonstrated a considerable downregulation of MexB expression in these isolates. This can be a useful antibacterial agent against multiple drug resistance P. aeruginosa infection. Conclusion: SeNP showed a major down-regulation in MexB expression in P. aeruginosa isolates. Keywords: BLIS, Sodium selenite, SeNps, MexB gene Citation: Salman MF, Al-Mudallal NHAL Ahmed ME. The effect of selenium nanoparticles on the expression of MexB gene of Pseudomonas aeruginosa Isolated from wound and burn infections. Iraqi JMS. 2024; 22(1): 79-92. doi: 10.22578/IJMS.22.1.10